(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
A pot experiment was carried out to evaluate the integrated effects of poultry litter, nitrogen and phosphorus on the growth and micronutrient (Fe, Zn and Cu) contents of arum (Colocasia esculenta L.) in the net house of the Department of Soil, Water and Environment, University of Dhaka. Height (76 cm), leaf number (5 no./plant), leaf area (1045.66 cm2/plant) and fresh (130.7 g/plant) and dry (14.35 g/plant) weights of leaf, stem, bulb and root were achieved highest in the combined application of decomposed poultry litter compost and nitrogen (PL2N40P0). The leaf area, and fresh and dry weights of leaf, stem, bulb and root varied significantly (p≤ 0.5). The concentration of iron, zinc and copper in different parts were measured the highest in the treatments (0.70%), (0.58%), (0.22%) for leaf; (0.83%), (0.96%), (0.99%) for stem; (0.74%), (0.09%), (0.05%) for bulb and (0.98%), (0.64%), (0.27%) for root, respectively. Generally, the concentrations of Fe, Zn and Cu were found to be the highest in PL4N20P15, PL4N0P15 and PL2N0P0 treatments, respectively. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(1): 11-18